2022
DOI: 10.3390/ijerph19052942
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extended Viewing Distance on Accommodative Response and Pupil Size of Myopic Adults by Using a Double-Mirror System

Abstract: Purposes: This study discussed the accommodative response and pupil size of myopic adults using a double-mirror system (DMS). The viewing distance could be extended to 2.285 m by using a DMS, which resulted in a reduction and increase in the accommodative response and pupil size, respectively. By using a DMS, the reduction of the accommodative response could improve eye fatigue with near work. Method: Sixty subjects aged between 18 and 22 years old were recruited in this study, and the average age was 20.67 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Meanwhile, the accommodation latency is a significant contributor to myopia. An increased accommodation latency induced by proximity to computer-use may exacerbate the progression of myopia [ 37 ]. Consistent with these previous findings, our MR analyses unequivocally demonstrated a causal association between leisure computer-use and myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the accommodation latency is a significant contributor to myopia. An increased accommodation latency induced by proximity to computer-use may exacerbate the progression of myopia [ 37 ]. Consistent with these previous findings, our MR analyses unequivocally demonstrated a causal association between leisure computer-use and myopia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the stimulation of farsightedness can reduce eye fatigue and discomfort, and improve visual comfort, thus slowing down the development of myopia [18]. Lin and Yeh et al [19,20]conducted a double-mirror system on adults and children respectively. The device can extend the image from 0.4 m away to 2.28 m away by using one concave mirror and one convex mirror.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no effective treatment has been established to control axial elongation or prevent the progression of myopia. Previous studies have reported that the autonomic nervous system innervates the iris, ciliary muscle, and choroid of the eye, and regulates accommodation, choroidal thickness (CT), choroidal rhythm, and pupillary responses, which are closely related to the development of myopia [23][24][25][26]. By regulating the choroid and sclera, the autonomic nervous system plays an important role in the development of myopia [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%